An inter-religious humanitarian response in the Central African Republic - Mahony, C (Refugee Studies Centre, University of Oxford, 2014)
Inter-religious action has played a key role in ensuring that social cohesion and inter-religious mediation remain on the international agenda in relation to response in the Central African Republic, where people’s faith is an integral part of their identity but where it has been manipulated in a horrific way